Continental divide : Heidegger, Cassirer, Davos - Gordon, Peter Eli (Harvard University Press, 2012)
This publication looks at Heidegger's and Cassirer's 1929 public conversation regarding what it means to be human. Gordon dissects the exchange itself to reveal that it was at core a philosophical disagreement.